Upaya Peningkatan Etika, Kreatifitas dan Disiplin di UPT SDN 067776 Medan Johor - Gaberiel Riskia Surbakti; Arief Marizki Purba (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Ethics of manners in learning in elementary school is very important to be applied to children from an early age, such as student etiquette when communicating with teachers and classmates. In addition, student creativity can be expressed through ischool mading, in the mading summarized all school activities, extracurricular activities can be pasted on the mading, student and teacher achievements can be displayed on the mading, even the works of students and teachers can also be pasted on the school mading. The character of discipline is based on the reason that there are now many deviant behaviors that are contrary to disciplinary norms. The application of discipline starts from simple things such as disposing of garbage according to its type and place. USU's partner teaching campus is one of the activities carried out by the University of North Sumatra together with educational institutions that establish partner relationships with the University of North Sumatra. This activity aims to improve the quality and quantity of students of each party, both USU and institutions that are USU partners. The MITRA-USU Teaching Campus 2023 is a continuation program of the pioneering teaching campus that was introduced in 2020, as proof of the campus's dedication in the success of national education. The teaching campus that will be held at UPT SDN 067776 Medan Johor involves a student from campus, Field Supervisors, and Civil Service Teachers from the teaching elements of UPT SDN 067776 Medan Johor. USU 2023 partner teaching campus is part of the Independent Campus Learning program, where in this program students will provide learning assistance in the form of extracurriculars. In addition, this program is also a test of the application of knowledge that has been obtained while studying at the University of North Sumatra. USU Partner teaching campus can also be juxtaposed with Field Lecture Practice (PKL).